Clinical Outcome of Posterior Instrumented Stabilization and Transpedicular Decompression in Patients Presenting with Thoracic or Lumbar Spinal Tuberculosis in a Tertiary Care Center: A Descriptive Cross-sectional Study - Dinesh Bhandari; Sabin Pokharel; Praja Pokharel; Sushil Paudel; Dinesh Kafle; Rohit Kumar Pokharel (Journal of Nepal Medical Association, 2024)
Introduction: Posterior instrumented stabilization is a commonly done surgery in spinal tuberculosis. This study aims to evaluate the clinical, radiological, and neurological outcomes of posterior instrumented stabilization and transpedicular decompression in thoracic and lumbar spinal tuberculosis.